THE REALITY OF SCIENCE TEACHERS IN ELEMENTARY EDUCATION IN A MUNICIPALITY OF MARANHAO - Feitosa Aguiar, Anarleth; Francisco Rodrigues Peres, João (Revista Gênero e Interdisciplinaridade, 2022)
The field education has a link with social subjects and their specificities, demanding from the teacher a differentiated work in relation to urban education, mediating the dialogue between theory and pedagogical practice, curriculum and reality of the field. In this sense, it was outlined as a general objective of the research, to analyze how the continuous training contributes to the development of the pedagogical practice of the teachers who work in the rural schools, and as specific objectives to identify the profile of the teachers who work from the 6th to the 9th year in the elementary school in the municipal school, to investigate how the teachers’ pedagogical practices are in the rural schools; understand how ongoing training for teachers working in rural schools is being carried out. For that, a qualitative descriptive research was carried out, the instruments used were interviews with teachers, and observations not participating in the school context. The research referrals showed that the teachers have training to work from the 6th to the 9th grade, but they work with several disciplines, aiming to complete the workload proposed by the secretariat, in addition, the courses offered do not contribute significantly, because they are not focused on the reality of the field and teachers feel excluded because everything is geared towards the urban area.